2020
DOI: 10.1186/s13068-020-01709-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a thermostable multi-domain xylanase-glucuronoyl esterase enzyme from Caldicellulosiruptor kristjanssonii incorporating multiple carbohydrate-binding modules

Abstract: Background: Efficient degradation of lignocellulosic biomass has become a major bottleneck in industrial processes which attempt to use biomass as a carbon source for the production of biofuels and materials. To make the most effective use of the source material, both the hemicellulosic as well as cellulosic parts of the biomass should be targeted, and as such both hemicellulases and cellulases are important enzymes in biorefinery processes. Using thermostable versions of these enzymes can also prove beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 75 publications
0
45
0
Order By: Relevance
“…To probe the ability of the PUL 17 CEs to aid GH action, we used them in conjunction with a commercially available xylanase in the degradation of a complex natural substrate. For this we chose Xyn11A, a GH11 endo-1,4-β-xylanase originating from the fungus Neocallimastix patriciarum, which has previously been used to study how CEs can boost xylanase depolymerization of complex xylan substrates (32,34,39). Ball-milled and freezedried corn cob biomass (5% w/v) was used as substrate, as it contains significant amounts of complex GAX (24).…”
Section: Carbohydrate Esterases Aid In Xylanase Hydrolysis Of Corn Cob Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…To probe the ability of the PUL 17 CEs to aid GH action, we used them in conjunction with a commercially available xylanase in the degradation of a complex natural substrate. For this we chose Xyn11A, a GH11 endo-1,4-β-xylanase originating from the fungus Neocallimastix patriciarum, which has previously been used to study how CEs can boost xylanase depolymerization of complex xylan substrates (32,34,39). Ball-milled and freezedried corn cob biomass (5% w/v) was used as substrate, as it contains significant amounts of complex GAX (24).…”
Section: Carbohydrate Esterases Aid In Xylanase Hydrolysis Of Corn Cob Biomassmentioning
confidence: 99%
“…In a recent study, we demonstrated that in two unique PULs from the gut bacterium Bacteroides ovatus and the aerobic soil bacterium Flavobacterium johnsoniae, CE1 and CE6 enzymes are found in "multicatalytic" enzymes, i.e., enzymes comprised of multiple catalytic domains on the same polypeptide (32). The combination of complementary enzymatic activities into single proteins with strongly enhanced activity has previously been shown mainly for enzyme activities targeting the main polysaccharide chain (20,33), but research on multicatalytic enzymes is often impeded by their large size and resulting difficulties in protein production (34). The benefit from combining "accessory" CE activities into a single enzyme is not as obvious as for glycoside hydrolases (GHs), where e.g., an endoacting enzyme can provide new chain ends for exo-acting enzymes that in turn reveal new sites of attack for the endo-acting enzymes and so forth.…”
mentioning
confidence: 99%
“…The inherent mobility between these catalytic modules allows the active sites to access different regions of a common polysaccharide substrate, enabling synergistic interactions between the different activities. This is exemplified by the degradation of acetylated xylans by enzymes displaying endo-xylanase and acetyl esterase activities ( 36 ). In GH145 enzymes, the two active sites target different AGPs, and thus, there is no obvious requirement for synergy to operate between the posterior and anterior catalytic centers.…”
Section: Resultsmentioning
confidence: 99%
“…Certain insights are established, for example, on enzymes in cellulosomes with domains of the polyspecific CBM32 family interacting with galactose, lactose, polygalacturonic acid, and N-acetyllactosamine (2). There are many examples where a functional role has been depicted for specific domains, while being unknown for others in multidomain architectures (3). Clearly, there are relatively few three-dimensional structures available of the more complex multidomain enzymes because of a number of challenges.…”
mentioning
confidence: 99%
“…Clearly, there are relatively few three-dimensional structures available of the more complex multidomain enzymes because of a number of challenges. One being the recombinant production of multimodular proteins containing interdomain linker regions prone to limited proteolysis, another is the dynamic flexibility inherent to the multimodular domain architectures (2,3).…”
mentioning
confidence: 99%